Orgasm-induced Seizures: A Case Report and Review of the Literature - Hüseyin Nezih Özdemir; Kamran Samedli; Figen Gökçay; Ahmet Gökçay (Türk Nöroloji Dergisi, 2021)
Certain types of stimuli can trigger epileptic seizures in patients with epilepsy. This phenomenon is defined as reflex seizure. Stimuli may be in visual, auditory, tactile, or cognitive forms, and orgasm may trigger epileptic seizures. A 42-year-old man was admitted to our department with orgasm-induced generalized seizures that had started 6 months ago. He was examined using electroencephalography and cranial magnetic resonance imaging, and was treated with levetiracetam and clobazam. His seizures were controlled well. In this article, we aim to present our case and review the literature on the subject.